Effect of Jujuboside A on Brain Ischemia / Reperfusion Injury Via Expression of Antiapoptotic Gene: - Movassaghi , Shabnam; Karimi, Alieh; Eydi, Akram; Sharifi , Zahra Nadia (Galen Medical Journal, 2022)
Background: Some studies highlighted the role of Jujuboside A as a potent antioxidant on ischemic neurons. However, the definitive effect of this substance on the change in the expression of the neuroprotective genes has not been clearly identified. Therefore, this study aimed to investigate the effects of Jujuboside A on the expression of proliferation-inducing genes and cell count enhancement in the hippocampus after the induction of transient global ischemia/reperfusion. Materials and Methods: This experimental study was performed on 24 male Wistar rats in four groups control, ischemia, vehicle, and Jujuboside A. Three days after induction of ischemia, the hippocampus of animals was removed and isolated from brain tissue. In order to investigate the results of the intervention, the expression of nuclear factor-ÎºB (NF-ÎºB), nerve growth factor (NGF), and Brain-derived neurotrophic factor (BDNF) genes were determined using real-time polymerase chain reaction. Results: The results showed that NGF expression was significantly higher in the Jujuboside A group than in the ischemic group (P<0.05). Moreover, the expression of BDNF in the Jujuboside A group was increased compared to the ischemic group. However, the expression of NFÎºB in the Jujuboside A group was lower than that of the ischemic and control groups, but these changes were not significant (P>0.05). Conclusion: Jujuboside A can increase the expression of NGF by promoting a protective effect on the hippocampus after transient global ischemia/reperfusion.